Corazon c. Aquino : early assessments of her presidential leadership and administration and her place in history - Abueva, Jose V. (Quezon City : University of the Philippines, 1993)
v.1
Keywords: Aquino, Corazon C., President, Philippines, 1933.; Philippine Politics and government 1986-1992.